PENGARUH PROMOSI DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN KREDIT RUMAH DI PT. HARI PELANGI PROPERTINDO - Tabroni Tabroni; Mamay Komarudin (Gapenas Publisher, 2021)
Apart from its main function as a place to live for its residents, it is also a measure of the existence of the owner's social status. People often buy houses for economic purposes, namely apart from being a place to live, as well as a place to do business activities. The purchase decision is a stage in consumer behaviour before the consumer finally decides to buy. The purchase decision is the stage of the purchasing decision process by the consumer actually making a purchase. The formulation of the problems in this study are 1) Is there an effect of promotion on home-buying decisions at PT. Hari Pelangi Propertindo at Griya Pelangi Sakina Housing ?. 2) Is there an effect of location on the decision to buy a house at PT. Hari Pelangi Propertindo at Griya Pelangi Sakina Housing ?. 3) Do together the promotion and location variables have an influence on consumer purchasing decisions to buy a house at PT. Hari Pelangi Propertindo on Griya Pelangi Sakina Housing?This research method uses a causal relationship. A causal relationship is a relationship that is cause and effect. So here there are independent variables (variables that influence) and dependent (influenced). The population in this study were 546 consumers who had bought housing in Griya Pelangi Sakina. To determine the sample taken using a non-probability sampling technique with the Slovin formula, the sample was 85 respondents.Based on the results of the calculation of the coefficient of determination partially, the contribution value of the effect of housing promotion on purchasing decisions is 32.2%. And the value of the correlation coefficient which states is quite strong with a value of 0.456. The results of the calculation of the coefficient of determination partially show that the contribution value of the effect of housing location on purchasing decisions is only 36.7%. And the value of the correlation coefficient which states that it is quite strong with a value of 0.478 with this result is that the location variable has an effect on consumer purchasing decisions. Based on the results of the processing, the R square value is 0.417 or 41.7%, while the remaining 58.3% is explained by other factors that are not explained or not thorough in this study. And the correlation coefficient value which states strong with a value of 0.646 with the results of the study showed that simultaneously the promotion and location variables have a significant effect on the decision to buy a house at PT. Hari Pelangi Propertindo at Griya Pelangi Sakina Housing